The Fathers of Massan: What an NHK Asadora Tells Us about Japanese Fatherhood. Issue 2 (3rd May 2020) - SturtzSreetharan, Cindi; Shibamoto-Smith, Janet S.
ABSTRACT: The NHK morning drama Massan features a male protagonist who unrelentingly pursues his dream of making Scotch whisky with Japanese-grown ingredients. After spending two years studying whisky-making in Scotland, he returns to Japan in 1921 with his Scottish wife, Ellie. Over the course of the drama, we follow Masaharu Kameyama as he develops as a craftsman, a husband, and a father. Drawing on explicit statements made by the characters about husbands and fathers, this paper focuses on the conduct and culture of fatherhood as represented in Massan . Focused attention is given to three central male characters in the drama: merchant Kinjirō Kamoi, aspiring artisan Ei'ichirō Kamoi, and Masaharu Kameyama himself. Specific attention is given to dialog that focuses on work, work–life balance, and stereotypical roles of husbands and wives. We find that due to the presence of a foreign wife, overt communications regarding husband–wife roles and fathers' responsibilities take place. Moreover, we discover that the story of one Japanese man and his foreign bride offer a bridge from the 1920s to present-day issues surrounding men's non-performance in the domestic sphere.